Electroencephalography (EEG) Frontal Alpha Asymmetry Index as an Indicator of Children’s Emotions in the Three Quran Learning Methods: Visual, Auditory, and Memory - Muhammad Khafid Syaifulloh; Muchtar Hanafi; Tonang Dwi Ardyanto; Nanang Wiyono; Pepi Budianto; Jumiatmoko Jumiatmoko (Iranian Journal of Psychiatry, 2022)
Objective: Quran memorization is familiar in Indonesia since early childhood (EC) education level and it is reported to have a positive effect on children’s emotional state. This study investigates how Quran memorization influences children’s emotions in a certain condition using Frontal Alpha Asymmetry (FAA) index.